Implementasi Manajemen Informasi Rekam Medis Berdasarkan Standar 8.4 Akreditasi Puskesmas di Puskesmas T Kota Tasikmalaya - Anisa Isnaini; Ida Sugiarti (Indonesian of Health Information Management Journal (INOHIM), 2023)
AbstractMinister of Health Regulation, 2015 number 46 of Primary Health Care Accreditation, is about recognizing independent institutions as administers accreditation by the Ministry of Health, held every three years after filling up the standards. Based on a preliminary study, T Primary Health Care had the first accreditation with the result of the 2017 Basic Status. Currently, T Public Health Center hasn't been re-accredited due to the impact of the Covid-19 pandemic. Medical record management is carried out by medical recorders in the special room, which is stored on shelves and boxes. There is a family medical record folder that still applies to personal medical records. T Primary Health Care stated that they had complete regulation because every two years routinely evaluated regulations and procedures, especially in the Management of medical records. The purpose of this study was to determine the alignment of the implementation of Medical Records Information Management (MIRM) in 8.4 Public Health Center Accreditation Standard for re-accreditation readiness by developing the quality of health services at T Primary Health Care in 2022. This research method used a case study approach with qualitative analysis. Result Research Organizing medical records in 8.4 standards of Medical Records Information Management (MIRM), T Public Health Center has tried to qualify the criteria. These include the available regulation and procedures related to the Management of Medical Records that are complete but haven't yet been ratified. As with each criterion, there are still discrepancies and obstacles in implementation. So the implementation of 8.4 standard Public Heath Center Accreditation is still not entirely by the regulations that have been made.Keywords: primary health care, primary health care accreditation, medical record managementAbstrakPeraturan Menteri Kesehatan Nomor 46 tahun 2015 menjelaskan Akreditasi Puskesmas merupakan pengakuan lembaga independen penyelenggara akreditasi ditetapkan oleh Menteri Kesehatan, setelah memenuhi standar yang diselenggarakan setiap 3 tahun. Berdasarkan studi pendahuluan Puskesmas T pernah melakukan akreditasi yang pertama dengan hasil status akreditasi dasar tahun 2017. Saat ini Puskesmas belum dilakukan re-akreditasi karena dampak pandemi Covid-19. Pengelolaan rekam medis dilakukan oleh Perekam Medis di ruang penyimpanan rekam medis yang disimpan pada rak dan kardus, memiliki map family folder tetapi masih menerapkan personal medical record. Puskesmas menyatakan regulasi telah lengkap, karena rutin melakukan evaluasi setiap dua tahun terkait Surat Keputusan (SK) dan Standar Prosedur Operasional (SPO) khususnya dalam pengelolaan rekam medis. Tujuan dilakukan penelitian untuk mengetahui pengelolaan keselarasan implementasi Manajemen Informasi Rekam Medis dalam standar 8.4 Akreditasi Puskesmas dalam kesiapan re-akreditasi sebagai upaya meningkatkan mutu pelayanan kesehatan di UPT Puskesmas T Tahun 2022. Penelitian digunakan dengan metode kualitatif pendekatan studi kasus. Hasil penelitian dalam penyelenggaraan rekam medis pada standar 8.4 Manajemen Informasi Rekam Medis, Puskesmas T telah berupaya memenuhi kriteria dalam standar tersebut. Diantaranya SK dan SPO terkait dengan pengelolaan rekam medis yang tersedia cukup lengkap, namun belum dilakukan pengesahan. Sebagaimana setiap kriteria masih terdapat ketidaksesuaian dan hambatan dalam pelaksanaanya. Sehingga implementasi dalam standar 8.4 Akreditasi puskesmas masih belum seluruhnya sesuai dengan regulasi yang telah dibuat.Kata Kunci: puskesmas, akreditasi puskesmas, pengelolaan rekam medis